Adsorption Efficiency of Fe(III) from Solution by Zeolite Y Synthesized from Rice Husk - Kulawong, Sittichai; Kulawong, Jittima (Naresuan University Journal: Science and Technology (NUJST); Vol 26 No 3 (2018): July-September 2018, 2018)
The purposes of this work were to prepare zeolite Y in sodium form (NaY) by using silica from rice husk, and to test the adsorption efficiency of the prepared NaY. The NaY was characterized by x-ray diffraction (XRD) and Brunauer, Emmett and Teller (BET) to confirm their structures and properties including isotherm adsorption and surface area. In addition, the adsorption efficiency of the NaY was tested in Fe(III) solution. The adsorption characteristics, contact time, initial concentration of iron solution, pH, and amount of adsorbent on the NaY, were studied. The time taken to reach equilibrium was 30 min. The amount of iron solution adsorbed increased as the pH increased, and the optimum values were pH 4.0-6.0. The adsorption capacity of the iron species in a solution at 30 °C was 57.80 mg/g, at 40 °C, 90.91 mg/g, and at 50 °C, 60.61 mg/g. The isotherms and isotherm constants were depicted from the results of the Langmuir and Freundlich adsorption. Adsorption isotherm data of the Fe(III) solution, when tested at 30 °C, could be well explained by the Langmuir model but that of Fe (III) tested at 40 °C and 50 °C were more related to the Freundlich model. The positive enthalpy (ΔH°) and the negative Gibbs free energy (ΔG°) suggested that the process of adsorption of the iron solution on the NaY was endothermic and spontaneous. The study of the kinetic adsorption model correlated with the pseudo-second order. Keywords: zeolite, adsorption, iron, rice husk